Stem Cell-based Therapies in Cardiovascular Diseases: From Pathophysiology to Clinical Outcomes - Papastamos, Charalampos; Antonopoulos, Alexios S.; Simantiris, Spyridon; Koumallos, Nikolaos; Theofilis, Panagiotis; Sagris, Marios; Tsioufis, Konstantinos; Androulakis, Emmanuel; Tousoulis, Dimitris (Current Pharmaceutical Design, 2023)
Over 20 years of intensified research in the field of stem cells brought about unprecedented possibilities in treating heart diseases. The investigators were initially fascinated by the idea of regenerating the lost myocardium and replacing it with new functional cardiomyocytes, but this was extremely challenging. However, the multifactorial effects of stem cell-based therapies beyond mere cardiomyocyte generation, caused by paracrine signaling, would open up new possibilities in treating cardiovascular diseases. To date, there is a strong body of evidence that the anti-inflammatory, anti-apoptotic, and immunomodulatory effects of stem cell therapy may alleviate atherosclerosis progression. In the present review, our objective is to provide a brief overview of the stem cell-based therapeutic options. We aim to delineate the pathophysiological mechanisms of their beneficial effects in cardiovascular diseases especially in coronary artery disease and to highlight some conclusions from important clinical studies in the field of regenerative medicine in cardiovascular diseases and how we could further move onwards.
Keywords: stem cell paracrine signaling